Takotsubo Cardiomyopathy With Inconspicuous Initial Electrocardiogram: A Potentially Serious Cardiac Pathology Related to Emotional Stress - Elsayed, Mohamed; Connemann, Bernhard J.; Dahme, Tillman; Tesfay, Temsgen; Gahr, Maximilian (Frontiers in Psychiatry, 2019)
Introduction: Takotsubo cardiomyopathy (TCM) is frequently associated with emotional or physical stress. Thus, patients with TCM might present primarily at a psychiatric clinic. Appropriate diagnosis and therapy may thus be delayed. Case report: A 43-year-old female patient presented as an emergency to the psychiatric outpatient clinic after experiencing severe work-related bullying. On admission, she complained of acute left thoracic chest pain as well as depressed mood, low energy, anhedonia, generalized anxiety, and sleep difficulties, present for several weeks. The initial electrocardiogram (ECG) was unremarkable; serum troponin levels, however, were markedly elevated. The patient was transferred to the department of cardiology. Via cardiac catheterization and MRI, an acute coronary syndrome was excluded and apical ballooning and left ventricular dysfunction, compatible with TCM, was found. Conclusion: Patients with acute psychopathology, recent emotional or physical stress, and acute cardiothoracic symptoms should receive immediate cardiological investigations. As the ECG may be normal in patients with TCM, concurrent measurement of the troponin serum level is recommended. Psychiatrists should consider TCM in patients who report recent stressful events accompanied by cardiothoracic symptoms.